The Influence of Information and Communication Technologies (ICTS) on Parents/ Adolescents Relationship - Ahiauzu, Levi Uche; Odili, Samuel Otunuya (Mediterranean Journal of Social Sciences, 2012)
The purpose of this study is to examine the influence of ICTs on parents/Adolescents relationships amongstaff families of Federal College of Education Technical Omoku. The objective of this study include to findout ways in which ICTs influence parents/adolescents relationships among academic staff families ofFederal College of Education Technical Omoku, to explore into the nature of social interactions that existbetween the parents and adolescent In the context of ICTs use, and also to examine the ways the parentsrelates with their children in respect of ICTs use. This study adopted survey design and selected a samplepopulation of 30 participants from the staff families of Federal College of Education Technical Omokuusing purposive sampling technique. The data obtained were analyzed with weighted mean, the resultsshow that the adolescents’ use of ICTs do not foster social pathology among them or hamper goodparents/adolescents relationships, though the parents are to be concerned with their children's ICTs basedactivities. The influence of ICTs on parents/adolescents relationship is a function of the level of theknowledge and use of technologies by both them, Adolescents ICTs use does not necessarily causerelational difficulties with parents nor lead to social pathology, nevertheless the parents should emphasizethe need for new media literacy among the adolescents in this ever changing new media environment thatcharacterize the knowledge-based economy.